Peningkatan Kapasitas Badan Permusyawaratan Desa dalam Menyusun Peraturan Desa tentang Technopreneurship - Rachman, Dedy Febry; Amri, Syaiful; Syamsurrijal (Insan Kreasi Media, 2025)
This community service aims to analyse the capacity building of the Village Consultative Body (BPD) in drafting village regulations on technopreneurship in North Jenggik Village, Montong Gading Sub-district. The background of this research is the potential for technopreneurship development in the village that has not been optimised due to the limited understanding and skills of the BPD in formulating supporting regulations. Using an interpretative descriptive qualitative approach, this research explores the BPD's understanding of technopreneurship, analyses the process and constraints of drafting village regulations, and identifies factors that influence BPD capacity building. Data were collected through in-depth interviews, participatory observations, document studies, and Focus Group Discussions (FGDs) with BPD members, village officials, and community leaders. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results community service are expected to provide a comprehensive picture of the condition of the BPD's capacity, the challenges faced, and formulate effective strategies to improve the BPD's ability to draft innovative and relevant perdes, so as to create an ecosystem conducive to the development of technopreneurship and encourage local economic progress in North Jenggik Village.